Comparing monomodality treatments of low-grade intracranial arteriovenous malformation at Hospital Kuala Lumpur between 2008 and 2011: A retrospective study - bin Rosli, Fadzlishah; Mohammed Haspani, Mohammed; Ab Ghani, Abdul (Asian Journal of Neurosurgery, 2016)
Introduction: Intracranial arteriovenous malformations (AVMs) of Spetzler-Martin grades (SMGs) I-III are treated using either monomodality treatments of microsurgical excision, embolization or stereotactic radiosurgery (SRS), or a combination of two or more of these treatment options. At Hospital Kuala Lumpur, we still practice monomodality treatments for AVMs of these three grades. In this study, we wanted to achieve an understanding whether monomodality treatments can achieve a satisfactory outcome of AVM nidi for patients, for up to 3 years, and to gather an objective data for AVM treatment for the Malaysian population. Subjects and Methods: This is a retrospective review of records study. The data are acquired from case notes of patients with intracranial AVM of SMGs I to III who underwent monomodality treatment at Hospital Kuala Lumpur between 2008 and 2011. The patients were followed up with imaging for up to 3 years from the date of treatment. A total of 81 patients were recruited in this study, where 30 underwent microsurgical treatment, 27 underwent embolization, and 24 underwent SRS. Results: Total obliteration of AVM nidus was achieved in 96.7% of patients who underwent microsurgery, 8.7% of patients who underwent embolization, and 79.2% of patients who underwent SRS. The modified Rankin scale (mRS) for all three groups showed an improving trend, with the microsurgery group showing the best improvement (from 70% at 3 months to 92.3% at 3 years showing favorable mRS scores). Conclusions: The AVM nidus obliteration for each treatment group is comparable to the meta-analysis published in 2011. Each modality had its own set of complications; however, most of the patients in all three groups had either static or improved mRS at the end of the 3-year follow-up.
Keywords: Arteriovenous malformation; embolization; Malaysia; microsurgery; stereotactic radiosurgery